Operators on positive semidefinite inner product spaces - Victor Bovdi; Tetiana Klymchuk; Tetiana Rybalkina; Mohamed A. Salim; Vladimir V. Sergeichuk; Bódi Viktor; Бовді Віктор; Клімчук Тетяна; Рибалкіна Тетяна; Сергейчук Володимир (Elsevier, 2020)
Abstract. Let U be a semiunitary space; ie, a complex vector space with scalar product given by a positive semidefinite Hermitian form<⋅,⋅>. If a linear operator A: U→ U is bounded (ie,‖ A u‖⩽ c‖ u‖ for some c∈ R and all u∈ U), then the subspace U 0:={u∈ U|< u, u>= 0} is invariant, and so A defines the linear operators A 0: U 0→ U 0 and A 1: U/U 0→ U/U 0. Let A be an indecomposable bounded operator on U such that 0≠ U 0≠ U. Let λ be an eigenvalue of A 0. We prove that the algebraic multiplicity of λ in A 1 is not less than the geometric multiplicity of λ in A 0, and the geometric multiplicity of λ in A 1 is not less than the number of Jordan blocks J t (λ) of each fixed size t× t in the Jordan canonical form of A 0. We give canonical forms of selfadjoint and isometric operators on U, and of Hermitian forms on U. For an arbitrary system of semiunitary spaces and linear mappings on/between them, we give an algorithm that reduces their matrices to canonical form. Its special cases are Belitskii's and Littlewood's algorithms for systems of linear operators on vector spaces and unitary spaces, respectively.
https://www.sciencedirect.com/science/article/abs/pii/S002437952030118X
Keywords: Positive semidefinite inner product spaces; Bounded operators; Belitskii's and Littlewood's algorithms; Pozitív félig végleges belső termékterek; Korlátozott operátorok; Belitski és Littlewood algoritmusai